Kontribusi Pidana Adat terhadap Pengembangan Sistem Keadilan Restoratif di Indonesia - Nur Sri Maryam DM (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Customary law existed long before Indonesia became independent. This system is a reflection of the noble values ​​believed in by indigenous peoples, such as mutual cooperation, kinship and respect for others. This research aims to analyze the principles of customary law that can be integrated into the formal justice system to support the development of a restorative justice system in Indonesia and the main challenges faced in implementing customary law as part of the restorative justice system in Indonesia and how to overcome them. The research method uses normative research methods and secondary data. Integration of customary law principles into the formal justice system can be done in various ways, such as adopting restorative principles, building hybrid models, increasing recognition of legality, involving communities, aligning with human rights, and applying local approaches in certain cases. The implementation of customary law as part of the restorative justice system in Indonesia faces various challenges, but with a strategic and adaptive approach, these challenges can be overcome.